Imaging of exercise-induced spinal remodeling in elite rowers - Frenken, M.; Schleich, C.; Radke, K. L.; Müller-Lutz, A.; Benedikter, C.; Franz, A.; Antoch, G.; Bittersohl, B.; Abrar, D. B.; Nebelung, S. (Journal of Science and Medicine in Sport, 2022)
Objectives: As in-vivo knowledge of training-induced remodeling of intervertebral discs (IVD) is scarce, this study assessed how lumbar IVDs change as a function of long-term training in elite athletes and age-matched controls using compositional Magnetic Resonance Imaging (MRI). Design: Prospective case-control study. Methods: Prospectively, lumbar spines of 17 elite rowers (ERs) of the German national rowing team (mean age: 23.9 ± 3.3 years) were imaged on a clinical 3.0 T MRI scanner. ERs were imaged twice during the annual training cycle, i.e., at training intensive preseason preparations (t0) and 6 months later during post-competition recovery (t1). Controls (n = 22, mean age: 26.3 ± 1.9 years) were imaged once at corresponding time points (t0: n = 11; t1: n = 11). Segment-wise, the glycosaminoglycan (GAG) content of lumbar IVDs (n = 195) was determined using glycosaminoglycan chemical exchange saturation transfer (gagCEST). Linear mixed models were set up to assess the influence of cohort and other variables on GAG content. Results: During preseason, IVD GAG values of ERs were significantly higher than those of controls (ERs(t0): 2.58 ± 0.27% (mean ± standard deviations); controls(t0): 1.43 ± 0.36%; p = 0.001), while during post-competition recovery, such differences were not present anymore (ERs(t1): 2.11 ± 0.18%; controls(t1): 1.89 ± 0.24%; p = 0.362). Conclusions: Professional elite-level rowing is transiently associated with significantly higher gagCEST values, which indicate increased lumbar IVD-GAG content and strong remodeling effects in response to training. Beyond professional rowing, core-strengthening full-body exercise may help to enhance the resilience of the lumbar spine as a potential therapeutic target in treating back pain.